Pseudoaneurysm complicating organ transplantation - Role of duplex sonography and MR angiography - Saha, BK; Rahman, T (Pulse, 2010)
We report a case of surgically proven pseudoaneurysm of transplanted renal artery. The 16 yr old patient had presented with rising creatinine for last 2 months and swelling of the face for 1 month. USG revealed a well defined cystic area in antero-medial aspect of transplanted kidney (near the renal hilum). Doppler & MR angiography confirmed a case of pseudoaneurysm. Repair of transplanted renal artery pseudoaneurysm with right internal iliac to common femoral artery bypass grafting done. Keywords: extra-renal pseudo aneurysm; renal transplantation; doppler ultrasound; MR angiography DOI: 10.3329/pulse.v3i1.6556 Pulse Vol.3(1) July 2009 p38-40